Misoprostol for the prevention of postpartum hemorrhage during home births in rural Lao PDR: establishing a pilot program for community distribution - Durham J; Phengsavanh A; Sychareun V; Hose I; Vongxay V; Xaysomphou D; Rickart K (Dove Medical Press, 2018)
Jo Durham,1 Alongkone Phengsavanh,2 Vanphanom Sychareun,2 Isaac Hose,1 Viengnakhone Vongxay,2 Douangphachanh Xaysomphou,2 Keith Rickart3 1Faculty of Medicine, School of Public Health, University of Queensland, Brisbane, Queensland, Australia; 2Faculty of Post-Graduate Studies, University of Health Sciences, Vientiane, Lao PDR; 3Communicable Diseases Branch, Department of Health, Brisbane, Queensland, Australia Purpose: The purpose of this study was to gather the necessary data to support the design and implementation of a pilot program for women who are unable to deliver in a healthcare facility in the Lao People’s Democratic Republic (PDR), by using community distribution of misoprostol to prevent postpartum hemorrhage (PPH). The study builds on an earlier research that demonstrated both support and need for community-based distribution of misoprostol in Lao PDR.Methods: This qualitative study identified acceptability of misoprostol and healthcare system needs at varying levels to effectively distribute misoprostol to women with limited access to facility-based birthing. Interviews (n=25) were undertaken with stakeholders at the central, provincial, and district levels and with community members in five rural communities in Oudomxay, a province with high rates of maternal mortality. Focus group discussions (n=5) were undertaken in each community.Results: Respondents agreed that PPH was the major cause of preventable maternal mortality with community distribution of misoprostol an acceptable and feasible interim preventative solution. Strong leadership, training, and community mobilization were identified as critical success factors. While several participants preferred midwives to distribute misoprostol, given the limited availability of midwives, there was a general agreement that village health workers or other lower level workers could safely administer misoprostol. Many key stakeholders, including women themselves, considered that these community-level staff may be able to provide misoprostol to women for self-administration, as long as appropriate education on its use was included. The collected data also helped identify appropriate educational messages and key indicators for monitoring and evaluation for a pilot program. Conclusion: The findings strengthen the case for a pilot program of community distribution of misoprostol to prevent PPH in remote communities where women have limited access to a health facility and highlight the key areas of consideration in developing such a program. Keywords: community distribution, misoprostol, postpartum hemorrhage, prevention, Lao PDR